PENGARUH INTENSITAS BERMAIN GAME ONLINE TERHADAP PENGENDALIAN DIRI SISWA SD NEGERI 2 GUNUNG BATU - Reza Malik Sofa; Hilman Hilmawan; Azahra Fajarianti; Nadia Larasati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has made online games one of the most popular forms of entertainment among elementary school children. This condition raises concerns because a high intensity of online gaming may affect students' self-control, which plays an important role in character development, discipline, and academic achievement. This study aimed to determine the level of online gaming intensity, the level of students' self-control, and the effect of online gaming intensity on the self-control of fifth-grade students at SD Negeri 2 Gunung Batu. This research employed a quantitative approach using a survey method involving 39 students. Data were collected through observation, closed-ended questionnaires, and documentation, and were analyzed using normality, linearity, heteroscedasticity, simple linear regression, and coefficient of determination tests. The results showed that online gaming intensity had a significant effect on students' self-control (Sig. = 0.000 < 0.05), contributing 50.4% to the variation in self-control. It can be concluded that online gaming intensity is one of the factors influencing students' self-control. These findings may serve as a reference for schools and parents in monitoring children's online gaming activities. Future studies are recommended to examine other factors that may influence students' self-control.